Characteristics of vestibular corrective saccades in patients with slow visual saccades, vestibular disorders and controls: A descriptive analysis. - Dario Andres Yacovino; Leigh Alexander Martin; Manuel Perez Akly; Timothy Carl Hain (PLoS ONE, 2018)
Our aim was to determine whether overt catch up saccades (OS) provoked by vestibular stimuli, as observed in the video head impulse test (vHIT), have comparable metrics as visually triggered horizontal saccades (VS), indicating a common saccadic brainstem generator.Three groups of patients were studied: patients with neurological disorders causing slow saccades (group 1, n = 12), patients with peripheral vestibular lesions (group 2, n = 43), and normal controls (group 3, = 24). All patients underwent vHIT and Videooculographic testing. OS velocity, acceleration, amplitude and duration and VS velocity in this group was compared between the groups.There was significant reduction in the velocity of visually guided saccades in group 1, as expected from the patient selection constraints of this study. Group 1 also exhibited saccades which were longer in duration and of reduced acceleration when compared to subjects without saccadic slowing to visual targets (Group 2 and 3). There were significant positive correlations between OS acceleration and amplitude in both normal saccade groups (2 and 3) which was not observed in the slow saccade group (1).The metrics of overt saccades measured by the vHIT in patients with slow saccades and normal controls are similar to visually guided saccades. This supports the hypothesis that overt saccades associated with vestibular stimuli and visually triggered saccades share common circuitry that controls metrics.